Current technologies and future directions for treating petroleum refineries and petrochemical plants (PRPP) wastewaters. Issue 5 (October 2019) - Jafarinejad, Shahryar; Jiang, Sunny C.
Graphical abstract: Highlights: PRPP wastewaters quality and discharge guidelines. Current WWTP technologies, configuration and operation in managing PRPP wastewaters. Advancements in PRPP WWTPs and future trends. Abstract: Water scarcity and wastewater management pose significant challenges to petroleum refineries and petrochemicals plants (PRPP). The escalating demand of petroleum products in pace with the world population growth and technological development requires new water management strategies that encourage reducing water consumption, reusing treated wastewater and remediating environmental impacts (R 3 ). New innovations and design of PRPP wastewater treatment plant (WWTP) are necessary to incorporate the principal of R 3 to meet both the industrial water needs and the environmental regulatory requirements. The goal of this review is to summarize the state of technologies for wastewater treatment in the PRPP in order to identify areas of future improvements. We begin with a systematic survey of water quality characteristics of PRPP discharge and the regulatory requirements for effluent water. We then examine the current WWTP technologies, configuration and operation in managing PRPP wastewaters, followed by discussion on PRPP WWTPs in Iran. Lastly, based on the gaps identified in the system analysis, we share our vision for future opportunities in improving the design and operation of PRPP WWTPs. Specifically, we recommend new hybrid technologies to increase treatment capacity, improve effluent water quality, and manage shock loadings of toxic materials and organics.